The Influence of Animated Videos on Critical Thinking Skills of Elementary School Students - Ahmad Khairul Fakhri; Pradana Chairy Azhar; Kiki Pratama Rajagukguk (ITScience (Information Technology and Science), 2025)
This study examined the influence of animated video utilization as an instructional medium on enhancing elementary school students' critical thinking abilities in science education, specifically focusing on human body organs in sixth grade. Animated videos, which integrate visual elements, textual information, and audio components, are practical pedagogical tools that facilitate educators' more engaging and comprehensive content delivery. Critical thinking is conceptualized as a higher-order cognitive process involving systematically evaluating information, problem-solving, decision-making, and formulating reasoned judgments based on logical analysis and evidence-based arguments. The research employed a quasi-experimental methodology with a pretest-posttest control group design. The sample consisted of 46 sixth-grade students who were randomly assigned to an experimental group and a control group. Both groups were administered a pretest to establish baseline critical thinking abilities. The experimental group received instruction through animated video media, whereas the control group was taught using conventional instructional methods. A posttest was conducted following the intervention to assess the students' progress. Data obtained from the pretest and posttest were analyzed using an independent samples t-test, following preliminary tests for normality and homogeneity of variance. The analysis results demonstrated a statistically significant improvement in the critical thinking skills of students exposed to animated video instruction compared to those who received traditional teaching. These findings suggest that the integration of animated video media in science education can serve as an effective strategy to foster critical thinking development among elementary school students.